VD_FINDINFO Jug / 2014 / 230 vom 5. März 2014 - VD Tribunal cantonal (2014)
PRÉSOMPTION D'INNOCENCE, VOLDROIT PÉNAL, INFRACTION D'IMPORTANCE MINEURE, COAUTEURDROIT PÉNAL | 139 CP, 172ter CP, 10 CPP (CH)